An initial magnet experiment using high-temperature superconducting STAR® wires. (1st December 2022) - Wang, Xiaorong; Bogdanof, Timothy J; Ferracin, Paolo; Ghiorso, William B; Gourlay, Stephen A; Higley, Hugh C; Kadiyala, Janakiram Kaushal; Kar, Soumen; Lee, Reginald; Luo, Linqing; Maruszewski, Maxwell A; Memmo, Robert; et al.
Abstract: A dipole magnet generating 20 T and beyond will require high-temperature superconductors such as Bi2 Sr2 CaCu2 O 8 − x and REBa2 Cu3 O 7 − x (RE = rare earth, rebco ). Symmetric tape round (star ®) wires based on rebco tapes are emerging as a potential conductor for such a magnet, demonstrating a whole-conductor current density of 580 A mm −2 at 20 T, 4.2 K, and at a bend radius of 15 mm. There are, however, few magnet developments using star ® wires. Here we report a subscale canted cos θ dipole magnet as an initial experiment for two purposes: to evaluate the conductor performance in a magnet configuration and to start developing the magnet technology, leveraging the small bend radius afforded by star ® wires. The magnet was wound with two star ® wires, electrically in parallel and without transposition. We tested the magnet at 77 and 4.2 K. The magnet reached a peak current of 8.9 kA, 78% of the short-sample prediction at 4.2 K, and a whole-conductor current density of 1500 A mm −2 . The experiment demonstrated a minimum viable concept for dipole magnet applications using star ® wires. The results also allowed us to identify further development needs for star ® conductors and associated magnet technology to enable high-field rebco magnets.